Local Heritage Values to Cope with Asia Future Shock In 2020 - Mulyaningsih Mulyaningsih (Jurnal Ilmu Sosial Politik dan Humaniora (Jisora), 2018)
A cultural and population changes have a biggest influence, the older Asian population, India became the second most influential country after the United States, the high investment costs, the lack of competence and competitiveness of Indonesian human resources as the second largest country after India resulted in the ASIA business situation and required Indonesia changed to become a country that counts in ASIA through the development of mindset and character based on local wisdom owned. The implementation of characteristic sharing organizational culture based on Pancasila philosophy and research based on local wisdom "sareundeuk saigel sabobot sapihanean, silih asih silih asuh silih, simbeuh at sunda with symbol of culture grandeur of kingdom Sumedang become base to change mindset and improve competence of competitiveness Indonesia facing ASIA future shock 2020. The methodology using a literature study review and research is descriptive of local wisdom as a local cultural collaboration received by both internal and external environments and its findings are recommended to decision-makers for practical action in solving problem Characteristics of sharing organizational culture implemented in the economic, cultural, social sector is the mindset to establish relationships with business actors through the use of culture, chinese trade, using the number of workers of low-educated classes, local raw materials, gender and anti-monopoly attitude through equal dimensions value harmonious, loyal, work together, survive and high spirit.